Signature of the anthropogenic impacts on the epipelagic microbiome of the North-Western Adriatic Sea (Mediterranean Sea) - Trapella, Giulia; Scicchitano, Daniel; Foresto, Lucia; Dell’Acqua, Andrea Nicoló; Radaelli, Elena; Turroni, Silvia; Rampelli, Simone; Corinaldesi, Cinzia; Palladino, Giorgia; Candela, Marco (Frontiers in Marine Science, 2024)
Introduction In our paper, we explored the impact of different anthropogenic stressors, namely, mussel farming, methane extraction platforms, and summer mass tourism, on the epipelagic microbiomes of the North-Western Adriatic Sea. Methods By 16S rRNA gene sequencing, we provided the epipelagic microbiome layout from selected sites corresponding to each of the considered impacts. As an unimpacted reference, we used already published 16S rRNA sequencing data. Results According to our findings, each one of the anthropogenic stressors resulted in a peculiar increase of specific epipelagic microbial components, including copiotrophic R-strategists and host-restricted bacteria, as well as some pathobiome components, the latter being detected exclusively in impacted sites. Particularly, potentially harmful pathogenic species such as Legionella impletisoli and Staphylococcus epidermidis have been detected in proximity to the mussel farms, and Escherichia coli and Campylobacter ureolyticus were present close to the methane extraction platform and at the summer mass tourism site, respectively. Particularly, C. ureolyticus is an emerging human gastrointestinal pathogen, capable of destroying intestinal microvilli. Discussion In addition to providing evidence supporting the existence of recognizable and impact-driven fingerprints on the epipelagic marine microbiome peculiar to the different anthropogenic stressors, our findings also raise concern about the ecological relevance of the observed changes, in terms of possible loss of ecosystem services and also for the potential release of pathogenic microorganisms in the environment.